Laryngeal cancer in Denmark: a nationwide longitudinal study based on register linkage data. Issue 7 (July 1990) - Guenel, P; Engholm, G; Lynge, E
Abstract : To identify high and low risk groups for laryngeal cancer in Denmark, all individuals aged 30-74 in the 1970 census were followed up over 10 years. Census data were linked with the Central Population Register to identify persons who died or emigrated during the follow up, and with the Danish Cancer Register to identify cases of laryngeal cancer. Individuals were categorised according to sex, age, and sociodemographic characteristics as declared on the census forms. A multivariate analysis was carried out by means of multiplicative Poisson models. The study showed that the risk of laryngeal cancer was strongly related to sociodemographic factors. The risk for skilled workers living in Copenhagen (relative risk (RR) 4.76, 95% confidence interval (CI) 3.61-6.28) was estimated to be almost five times higher than the risk for men self employed in agriculture and living in rural areas. The variation in the risk of laryngeal cancer is not fully explained by known variations in tobacco and alcohol consumption, and this study highlights additional risk factors particularly related to occupation and marital state.